KAZAKH AND TATAR BOOK TRADE IN THE STEPPE REGION IN THE LATE 19TH AND EARLY 20TH CENTURIES (Journal of history, 2026)
The article examines the features of the Muslim (Kazakh and Tatar) book trade in the Steppe region in the late 19th and early 20th centuries. Using a combination of special historical methods (comparative-historical method, critical analysis of texts) and interdisciplinary approaches (Islamic discourse), the author analyzes the general trends in the development of the book trade and identifies its regional characteristics.      The article explores the impact of the book trade on the cultural development of society, including the specific features of cultural leisure in a particular city, the need for reform in the Muslim education system, and the introduction of advanced scientific and cultural achievements.       A variety of archival and Arab scripture printed and handwritten sources have allowed us to establish not only the names and surnames of the owners of bookstores, but also to understand the range of books available to customers. For example, the works of Abai Kunanbaiev, Shakarim Kudaiberdiiev, Akhmet Baitursynov, and Mustakim Maldybaiev were in high demand in Kazakh bookstores. Moreover, some of these works were published in the Steppe region. In particular, at the publishing house «Zhärdem» in Semipalatinsk. Tatar bookstore owners mainly offered textbooks, religious, artistic, and scientific literature published in Kazan, Orenburg, Ufa, and other cities.
Keywords: Steppe region, Petropavlovsk, Akmolinsk, Semipalatinsk, Zaisan, Kusnanai, book trade, merchants, new method, zhärdem.